Human settlement of Mars in the context of the Outer Space Treaty 1967 - Sinclair, Amy Laura (Department of Public Law, 2019)
This mini-dissertation asks whether international law permits the human settlement of Mars. The paper is inspired by the public goal of aerospace entrepreneur and futurist Elon Musk to transport human crew to Mars within 10 years. His company SpaceX, as well as other key players in the global aerospace industry, are rapidly developing the technological capacity and business case for the exploitation of off-world resources. Human settlement of Mars is no longer confined to the realm of science fiction. It raises questions of international law that, until very recently, were dismissed as fantastic. The Outer Space Treaty (1967) has found widespread acceptance; however Arts I and II dealing with rights to ‘use’ of space and banning ‘national appropriation’ are vague. The interpretation of these sections has proved controversial in light of proposals by private companies to exploit space resources by mining asteroids. This debate informs my reflections on whether human settlement of another planet might violate the Outer Space Treaty – but it is not quite the whole story. The opinions of leading space law experts on the question of human settlement of Mars opinions are frequently sought in the popular media, especially in the aftermath of any announcement of SpaceX or Elon Musk. However, the topic is yet to be dealt with in an in-depth academic setting. The paper will address: • Chapter II: Does the establishment and conduct of a human settlement fall within the freedom of activities anticipated in Article I Outer Space Treaty? • Chapter III: Does Article I oblige settlers to share the profits (if any) of their activities with Earth? • Chapter IV: Does the establishment of the settlement constitute an appropriation within the terms of Article II Outer Space Treaty? • Chapter V: Are settlers entitled to exclude others from the settlement?